Profiling endogenous adrenal function during veno-venous ECMO support in COVID-19 ARDS: a descriptive analysis - Baumgartner, Clemens; Wolf, Peter; Hermann, Alexander; König, Sebastian; Maleczek, Mathias; Laxar, Daniel; Poglitsch, Marko; Domenig, Oliver; Krenn, Katharina; Schiefer, Judith; Kautzky-Willer, Alexandra; Krebs, Michael; et al. (Frontiers in Endocrinology, 2024)
Background: Prolonged critical illness is often accompanied by an impairment of adrenal function, which has been frequently related to conditions complicating patient management.The presumed connection between hypoxia and the pathogenesis of this critical illness related corticosteroid insufficiency (CIRCI) might play an important role in patients with severe acute respiratory distress syndrome (ARDS). Since extracorporeal membrane oxygenation (ECMO) is frequently used in ARDS, but data on CIRCI during this condition are scarce, this study reports the behaviour of adrenal function parameters during oxygenation support with venovenous (vv)ECMO in COVID-19 ARDS.Methods: Eleven patients undergoing vvECMO due to COVID-19 ARDS at the Medical University of Vienna, who received no concurrent corticosteroid therapy, were retrospectively included in this study. We analysed the concentrations of cortisol, aldosterone, and angiotensin (Ang) metabolites (Ang I-IV, Ang 1-7 and Ang 1-5) in serum via liquid chromatography/tandem mass spectrometry before, after one day, one, and two weeks during vvECMO support, and conducted correlation analyses between cortisol and parameters of disease severity.Cortisol concentrations appeared to be lowest after initiation of ECMO and progressively increased throughout the study period. Higher concentrations were related to disease severity and correlated markedly with interleukin-6, procalcitonin, pH, base excess, and albumin during the first day of ECMO. Fair correlations during the first day could be observed with calcium, duration of critical illness, and ECMO gas flow. Angiotensin metabolite concentrations were available in a subset of patients, and indicated a more homogenous aldosterone response to plasma renin activity after one week of ECMO support.Oxygenation support through vvECMO may lead to a partial recovery of adrenal function over time. In homogenous patient collectives, this novel approach might help to further determine the importance of adrenal stress response in ECMO and the influence of oxygenation support on CIRCI.